2016
DOI: 10.1111/tri.12870
|View full text |Cite
|
Sign up to set email alerts
|

Use of direct-acting agents for hepatitis C virus-positive kidney transplant candidates and kidney transplant recipients

Abstract: In some parts of the world, hepatitis C virus (HCV) infection remains a huge problem for kidney transplant candidates and kidney transplant (KT) recipients. Until 2 years ago, anti-HCV treatment for the general population relied on pegylated alpha-interferon plus ribavirin, but led to a sustained viral response (SVR) in <50% of cases. This treatment was contraindicated in KT patients because of acute-rejection issues and was poorly tolerated in patients with end-stage renal disease (ESRD). Over the last year, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 65 publications
0
4
0
2
Order By: Relevance
“…This dismal scenario has dramatically changed with the advent of direct antiviral agents (DAAs), allowing the design of all‐oral IFN‐α‐free regimens . Sofosbuvir (SOF) is a pan‐genotypic nucleotide analog with a potent inhibitory effect on the viral NS5B polymerase .…”
Section: Introductionmentioning
confidence: 99%
“…This dismal scenario has dramatically changed with the advent of direct antiviral agents (DAAs), allowing the design of all‐oral IFN‐α‐free regimens . Sofosbuvir (SOF) is a pan‐genotypic nucleotide analog with a potent inhibitory effect on the viral NS5B polymerase .…”
Section: Introductionmentioning
confidence: 99%
“…Böbrek nakli sonrası HCV tedavisinde ise IFN kullanmak mümkün olmuyordu. Çünkü IFN immün sistemi aktive ederek akut rejeksiyon riski ortaya çıkarıyordu (2,3). Özellikle son 4 yılda birçok araştırma ile etkinliği kanıtlanan direkt etkili antiviral kombinasyonlar ise HCV enfeksiyonunun uzun süreli tedavisini, hatta eradikasyonunu mümkün kıldı.…”
Section: Discussionunclassified
“…Yeni çıkan direkt etkili antiviral ilaçların kullanıma girmesi ile nakil sonrası HCV tedavisinde büyük aşama elde edilmiş-tir. Nakil öncesi mevcut olan HCV için viral yükün ortadan kaldırılması tercih edilmektedir (1,2). Böbrek nakli sonrası dönemde gösterilen HCV enfeksiyonunun tedavisi ise daha özenli bir yaklaşım gerektirir.…”
Section: Introductionunclassified
“…Rostaing et al[ 74 ] recently reviewed the treatment of HCV infection in kidney transplant candidates with poor renal function or on dialysis. Saxena et al[ 75 ] reported the efficacy of sofosbuvir in association with ribavirin in 73 patients with an eGFR < 45 mL/min, and SVR was achieved in 83% of patients.…”
Section: Effects Of Daas In Patients With Esrd and On Waiting Lists Fmentioning
confidence: 99%